Angiomodulin, a marker of cancer vasculature, is upregulated by vascular endothelial growth factor and increases vascular permeability as a ligand of integrin αvβ3. (16th April 2014) - Komiya, Eriko; Sato, Hiroki; Watanabe, Naoko; Ise, Marii; Higashi, Shouichi; Miyagi, Yohei; Miyazaki, Kaoru
Abstract Angiomodulin (AGM) is a member of insulin‐like growth factor binding protein (IGFBP) superfamily and often called IGFBP‐rP1 or IGFBP‐7. AGM was originally identified as a tumor‐derived cell adhesion factor, which was highly accumulated in blood vessels of human cancer tissues. AGM is also overexpressed in cancer‐associated fibroblasts (CAFs) and activates fibroblasts. However, some studies have shown tumor‐suppressing activity of AGM. To understand the roles of AGM in cancer progression, we here investigated the expression of AGM in benign and invasive breast cancers and its functions in cancer vasculature. Immunohistochemical analysis showed that AGM was highly expressed in cancer vasculature even in ductal carcinoma in situ (DCIS) as compared to normal vasculature, while its expression in CAFs was more prominent in invasive carcinomas than DCIS. In vitro analyses showed that AGM was strongly induced by vascular endothelial cell growth factor (VEGF) in vascular endothelial cells. Although AGM stimulated neither the growth nor migration of endothelial cells, it supported efficient adhesion of endothelial cells. Integrin αvβ3 was identified as a novel major receptor for AGM in vascular endothelial cells. AGM retracted endothelial cells by inducing actin stress fibers and loosened their VE‐cadherin‐mediated intercellular junction. Consequently, AGM increased vascular permeability both in vitro and in vivo. Furthermore, AGM and integrin αvβ3 were highly expressed and colocalized in cancer vasculature. These results suggest that AGM cooperates with VEGF to induce the aberrant functions of cancer vasculature as a ligand of integrin αvβ3.